Gut Microbiome Dysbiosis and Disease Correlation: The Factors Influencing the Gut Microbiota’s Composition and Function along with Possible Mechanisms to Potential Therapeutic Strategies - Renuka Ekka; Vaishali Tiwari; Shashikala Bhagat; Sumathi Poleboina; Bharti Ahirwar (Disease and Health Research: New Insights Vol. 11, 2024)
The human digestive system contains trillions of bacteria living in the gut microbiota, which is incredibly diverse. The gut microbiome begins to form and multiply from birth, and changes in its composition are primarily caused by a variety of genetic, dietary, and environmental variables. Dysbiosis is defined as a shift in the makeup and function of the gut microbiota or an unbalanced microbial community structure from the normal state. This can affect immunological responses, digestion, and metabolism as well as intestinal permeability. An imbalance in the gut microbiota can induce a pro-inflammatory state that can lead to a variety of diseases, including gastrointestinal and metabolic disorders, immunological disorders, neuropsychiatric disorders, colorectal cancer (CRC), irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD), along with extra-intestinal conditions like Type 1 and 2 diabetes, obesity, etc. The current review addresses how nutrition and the environment impact the structure and function of gut microbes and elucidates the significance of gut microbiota in preserving human health. The numerous factors that affect the human microbiome are discussed in this overview along with their cause-and-effect relationships to current investigations that have looked at the connection between gut microbiome dysbiosis and disease development. A more effective treatment strategy and a potentially helpful tool in the dysbiosis gut microbiome restoration. Strategies have been studied to achieve this goal, including phages, extracellular vesicles, immunological regulation, microbial metabolites, dietary treatments, fecal microbiota transplantation (FMT), prebiotics and probiotics.